A standard computable general equilibrium (CGE) model in GAMS - Lofgren, Hans; Harris, Rebecca Lee; Robinson, Sherman (International Food Policy Research Institute, 2001)
Computable general equilibrium (CGE) models are used widely in policy analysis. The purpose of this paper is to contribute to and facilitate the use of CGE models. The paper includes a detailed presentation of a “standard” CGE model (an equation-by-equation description) and its required database. It incorporates features developed in recent years in research projects conducted at IFPRI. These features, which are of particular importance in developing countries, include household consumption of non-marketed (or “home”) commodities, explicit treatment of transaction costs for commodities that enter the market sphere, and a separation between producing activities and commodities that permits any activity to produce multiple commodities and any commodity to be produced by multiple activities. The paper discusses the implementation of the model in GAMS (the General Algebraic Modeling System) and is accompanied by a self-extracting zip file, which includes the GAMS files for the model, sample databases, simulations, solution reports, and a SAM aggregation program. Although the paper provides a standardized framework for analysis, the analyst is not forced to make “one-size-fits-all” assumptions. The GAMS code is written in a manner that gives the analyst considerable flexibility in model specification.